The Formulation and Evaluation of Facial Wash containing Snow Mushroom (Tremella fuciformis) Extract - Astridani Rizky Putranti; Krisyanti Budipramana; Mellynia Fortuna Salim (Universitas Muhammadiyah Malang, 2022)
The aims of this study were to determine and evaluate the results of the physicochemical characteristic of snow mushroom (Tremella fuciformis) facial wash, and to determine the acceptability of the snow mushroom (Tremella fuciformis) extract facial wash which has the best physicochemical characteristics. In this study, the extraction of snow mushroom (Tremella fuciformis) used UAE (Ultrasound-Assisted Extraction) and ethanol as solvent with various concentrations, 96% (F1), 75% (F2), and 50% (F3). Furthermore, the extract will be formulated into facial wash and evaluated for physicochemical characteristics. The parameters of physicochemical characteristics include organoleptic, pH, density, viscosity, spreadability, and foamability. The difference in the concentration of ethanol as menstruum of snow fungus (Tremella fuciformis) extraction did not significantly affect the organoleptic composition of facial wash, but it did affect the physicochemical characteristics of facial wash, where higher ethanol concentrations resulted in lower pH, higher density and viscosity, smaller spreadability, and foamability that meets specifications. The results of the evaluation of physicochemical characteristics showed that F1 had the best specifications and continued hedonic testing to determine the acceptability of snow mushroom (Tremella fuciformis) extract facial wash. The results of the hedonic test on F1 showed good acceptance regarding the parameters of appearance, foam, and effects after using facial wash; as well as sufficient acceptability related to aroma and viscosity parameters.